Comparative study of the Antibody Responses to Streptococcus pyogenes between school Children carriers and patients with Tonsillitis - Abd Al-Kareem, Fadwa; Abbas, Aruba; Hussein, Median (Iraqi Journal of Science, 2023)
This study is designed to evaluate the immune status of patients and schoolchildren with respect to Streptococcus pyogenes. A prospective study was conducted to investigate antibody against GAS in children patients and asymptomatic healthy carriers in serum samples with tonsillitis and compare antibody response (ASO) between patients and healthy carriers with tonsillitis.Tonsillar swabs were obtained to detect the presence of GAS and blood samples were collected to determine elevated ASO titer in serum.A total of 376 sample patients and asymptomatic healthy carriers were included in this study, 142 (37.7%) samples are GABHS positive, included 80 (56.3%) patients and 62 (43.6%) asymptomatic healthy carriers. The finding of a significant relationship between ASO positive and GABHS carriage and patients indicated that ASOT measurement might be used together with throat culture to identify GABHS carriers and GABHS patients.The value of ASOT varies with the age of the subject, and the most pronounced differences are between the values of preschool age children and school age children. The upper limits of normal values for these groups were as follows: preschool age (100) and school age (170).Recently infected children showed raised ASO antibody titer than the carrier. But this study present elevated of ASOT in asymptomatic healthy carriers indicated recent infection or past infection then this children recovery from disease but remain record titer of antibody.